Nutritional Evaluation of Pulses and Soybean Meal in Dogs - Dhaliwal, J. K.; Sethi, A.P. S.; Sikka, S. S. (Indian Journal of Animal Nutrition, 2018)
Six adult Labrador dogs were used in this experiment to evaluate total tract apparent nutrient digestibility and energy values of some protein feedstuffs. Seven digestibility trials were conducted. The 30% of basal diet was replaced with test ingredient which included one conventional feed ingredient i.e. soybean (Glycine max) meal (SBM) and five pulses (black-eyed pea or roongi (Vigna unguiculata), red lentil or masoor(Lens culinaris) dhuli, moong (Vigna radiata) dhuli, split bengal gram or chana (Cicer arietinum) dal and split black gram or urad (Vigna mungo) dhuli dal). The prepared mash diets were cooked and then fed to each dogas per their body weight and nutrient requirement.The difference/ substitution method was used to estimate total tract apparent nutrient digestibility and energy values of these six protein ingredients. The DM, OM, CP, EE digestibility of masoor dhuli dal was significantly (P